2012
DOI: 10.1542/peds.2012-0147
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Diagnosis of Health Care–Associated Infections in the NICU

Abstract: Health care−associated infections in the NICU are a major clinical problem resulting in increased morbidity and mortality, prolonged length of hospital stays, and increased medical costs. Neonates are at high risk for health care−associated infections because of impaired host defense mechanisms, limited amounts of protective endogenous flora on skin and mucosal surfaces at time of birth, reduced barrier function of neonatal skin, the use of invasive procedures and devices, and frequent exposure to broad-spectr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(65 citation statements)
references
References 37 publications
2
58
0
1
Order By: Relevance
“…This theory could be further supported by the observation that CoNS, as a member of commensal skin flora, was the most common pathogen isolated in PICC-associated CLA-BSI. 14,18,23 As a result, we designed this study, and our hypothesis was that the prolonged duration resulted in increased frequency of peripheral venipunctures. With the increased frequency of peripheral venipunctures, the possibility of transient bacteremia increased and it was more likely to cause bacteria colonization on PICC and subsequent CLA-BSI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This theory could be further supported by the observation that CoNS, as a member of commensal skin flora, was the most common pathogen isolated in PICC-associated CLA-BSI. 14,18,23 As a result, we designed this study, and our hypothesis was that the prolonged duration resulted in increased frequency of peripheral venipunctures. With the increased frequency of peripheral venipunctures, the possibility of transient bacteremia increased and it was more likely to cause bacteria colonization on PICC and subsequent CLA-BSI.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational age was categorized as <32 weeks or !32 weeks. Birth weight was categorized as <1500 g or !1500 g. 1,23 Chronological age was grouped as 7 days or >7 days. The PICC duration was divided into three groups d 10 days, 11e20 days, and >20 days d in univariate analysis, and the frequency of peripheral venipunctures was grouped as <6 times and !6 times.…”
Section: Data Collectionmentioning
confidence: 99%
“…It has been reported that invasive nosocomial infections predominantly occur in children younger than 1 year of age, with an incidence of 14.7 per 100,000, versus 0.3-1.0 per 100,000 in older children [5] and the risk factors associated with an increased rate of infections in the neonatal intensive care unit (NICU) were suggested. These included the presence of invasive devices, exposure to broad-spectrum antibiotic agents, the use of parenteral nutrition, overcrowding and poor staffing ratios [12]. …”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Pediatric hospital patients are especially vulnerable to adverse outcomes from AR infections due to factors such as immature immune systems, acquired or congenital immunodeficiencies, need for chronic parenteral nutrition, and congenital anomalies. 8 The unique impact HAIs have on pediatric patients is underscored by the fact that rates of device-associated infections are higher in some pediatric unit types than in corresponding adult units, despite a lower device utilization ratio.…”
mentioning
confidence: 99%